2008
DOI: 10.1007/s00134-008-1356-5
|View full text |Cite
|
Sign up to set email alerts
|

Serum selenium and glutathione peroxidase-3 activity: biomarkers of systemic inflammation in the critically ill?

Abstract: Systemic inflammatory response syndrome and MODS were associated with early decreases in [Se] and [GPx-3]. Low [Se] and [GPx-3] after ICU admission had a predictive value for SIRS, which may aid future selection of patients who could benefit from Se supplementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
82
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 36 publications
7
82
1
4
Order By: Relevance
“…Also, those with low levels of selenium or GPx had a significantly higher risk of developing SIRS and MODS. The authors discuss a possible mechanism based on the fact that a deficiency of selenium could activate the nuclear transcription factor kappa B (NFk-B) and promote vasoconstriction and coagulation, as seen in SIRS [18].…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
“…Also, those with low levels of selenium or GPx had a significantly higher risk of developing SIRS and MODS. The authors discuss a possible mechanism based on the fact that a deficiency of selenium could activate the nuclear transcription factor kappa B (NFk-B) and promote vasoconstriction and coagulation, as seen in SIRS [18].…”
Section: Selenium and Cardiovascular Diseases: From Prevention To Carmentioning
confidence: 99%
“…Despite intervention measures in SIRS cases using Se supplementation (40 lg/day), patients with low initial Se levels tended to stay low and this was particularly true in patients whose condition worsened. Another study that confirmed the association between Se levels and SIRS outcome demonstrated that GPX3 activity was decreased in patients with severe SIRS (154). Based on the correlative data just described, there has emerged an interest in the use of Se supplementation as an intervention of SIRS.…”
mentioning
confidence: 92%
“…The broad definition of SIRS and the numerous underlying causes make this an especially difficult condition to characterize and treat. SIRS is characterized by an early decrease in Se status as demonstrated by low plasma Se, GPX3 activity, and SELP levels (73,154,214). The changes in Se status observed during SIRS suggest that this nutritional factor may serve as a potential biomarker or prognostic indicator for intensive care unit patients with SIRS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During CPB there is an increased production of reactive oxygen species (ROS) and reactive nitrogen oxide species (RNOS) initiated by preventing an excessive build-up of SOD and hydrogen peroxide (Figure 4-1). Their activity is dependent on appropriate levels of essential trace elements such as selenium for GPx activity, 183 and copper and zinc for SOD activity. 184,185 Reductions of selenium in non-cardiac critically ill patients have been associated with increases in mortality and morbidity, 5,128 while a recent study of adult cardiac surgical patients indicated that decreases in selenium were associated with increased postoperative multi-organ failure (MOF).…”
Section: Introductionmentioning
confidence: 99%